The first Tuvan-language site on the Internet - Damba-Huurak, Orlan D. (The New Research of Tuva, 2010)
"Eki hünnüŋ mendizi-bile, ergim öŋnük!" - these are the words that meet visitors on the first Internet site completely made in the Tuvan language: http://orlan.tuva.ru that started in 2009. Its author - a well-known Tuvan TV reporter Orlan Damba-Huurak - represents his brainchild to the readers of our magazine.